2016
DOI: 10.7763/ijiet.2016.v6.824
|View full text |Cite
|
Sign up to set email alerts
|

Motivations and Challenges in MOOCs with Eastern Insights

Abstract: Abstract-Massive open online courses (MOOCs) are the latest e-learning initiative to attain widespread popularity in the world. Unfortunately, nearly all of these studies are built from western insights. Thus, there is a need for a thematic and practical analysis of related studies to bring a better understanding of MOOCs with eastern insights. In this paper, a study is conducted focusing on the use of MOOCs from the eastern perspective. Our primary goal is to summarize the motivations and challenges of using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 7 publications
0
22
1
2
Order By: Relevance
“…However, compared to other studies (Radford et al, 2015;Stokes, Towers, Jinks & Symington, 2015;Zhong et al, 2016), earning credits and the relationship with participants' program, which can be assimilated to educational pursuit in previous studies, are not as important as friends when it comes to stirring students to enroll into a MOOC. For instance, 53.7% were stimulated by the connection of the course to their program, but 79.5% did not enroll to earn credits.…”
Section: Employment Statusmentioning
confidence: 99%
See 3 more Smart Citations
“…However, compared to other studies (Radford et al, 2015;Stokes, Towers, Jinks & Symington, 2015;Zhong et al, 2016), earning credits and the relationship with participants' program, which can be assimilated to educational pursuit in previous studies, are not as important as friends when it comes to stirring students to enroll into a MOOC. For instance, 53.7% were stimulated by the connection of the course to their program, but 79.5% did not enroll to earn credits.…”
Section: Employment Statusmentioning
confidence: 99%
“…In this study of learners enrolled in a MOOC developed by a Chinese university, Zhong et al (2016) found that participants (55%) mostly chose MOOC because it appeared interesting and a good way to obtain knowledge. Twenty seven percent selected their MOOC to gain new skills necessary for job search; and 85% mentioned the convenience of working at their own time and location (Zhong et al, 2016).…”
Section: Motivation For Enrollingmentioning
confidence: 99%
See 2 more Smart Citations
“…Amongst a number of factors behind this challenge, a lack of motivation, particularly learner intrinsic motivation is considered as one of the major components (Espinosa, Sepúlveda, & Montoya, 2015;Zhong et al, 2016). Individual learners who lack intrinsic motivation often leave the course before completing it and this can significantly increase dropout rates.…”
Section: Statement Of the Problemmentioning
confidence: 99%